Evaluation of Subdermal Birth Control Implants Use among Married Women of Reproductive Age in a Metropolitan City of Bangladesh - Islam, Baishakhi; Jannat, Tamanna; Begum, Arifa; Sharmee, Tania Hussain; Luna, Mahfuja Khanam (Mediscope, 2022)
Background: Long-term hormonal birth control implant is the way of achieving optimal birth spacing in our country where high birth rate is one of the major concerns. Aims & objectives: To evaluate the knowledge, attitude, usage & feedback that influences the use of subdermal implants. Methods: This cross-sectional study was conducted in different maternity centers in Dhaka city. A total of 200 married women of reproductive age (18-45 years) were included in the study, whereas women beyond this age range & having co-morbidities were excluded. Data were collected through a standardized questionnaire and analyzed using Microsoft Excel 2007 spreadsheet. Results: In this study, 60% of women were in the age group ranging from 27 to 35 years, 27.5% were educated up to SSC/HSC level, 37% were housewives, 46% had poor socioeconomic conditions and 57.5% came from rural areas. The majority (71%) had heard about implants and 29% didn’t know about the implant. Overall attitude was positive in 33% of respondents. About 39.70% quit due to desired pregnancy. Among 59% of users, there was a negative attitude due to some adverse effects. Conclusion: Despite some negative attitudes regarding subdermal implants, the use of this method is progressively gaining positivity regarding knowledge, attitude and other associated factors among women of reproductive age. Mediscope 2022;9(2): 60-67